Diagnostic value of simultaneous 99mTc-sestamibi/123I-BMIPP imaging parameters for predicting the improvement of left ventricular wall motion after acute myocardial infarction using CZT SPECT system. (14th October 2021) - Hida, S; Fujita, Y; Hatano, T; Morishima, T; Yamashita, J; Murata, N; Ito, R; Chikamori, T
Abstract: Background: Although the presence of 99mTc-sestamibi/123I-BMIPP-mismatch, the reverse redistribution (RR) of 99mTc-sestamibi and RR of 123I-BMIPP in patients with acute myocardial infarction (AMI) are known to significant markers for predicting the improvement of LV wall motion in the infarcted territory in chronic phase, few studies were performed to analyze them by simultaneous dual-isotope imaging using cadmium-zinc-telluride (CZT) SPECT system. Purpose: The purpose of this study was to evaluate whether the presence of 99mTc-sestamibi/123I-BMIPP-mismatch or RR of 99mTc-sestamibi, RR of 123I-BMIPP make better prediction of the improvement of LV wall motion in the infarcted territory. Methods: We evaluated 42 consecutive patients with AMI who had undergone both dual-isotope SPECT in acute phase and stress myocardial SPECT using 99mTc-tracers in chronic phase by Discovery NM530c. The presence of 99mTc-sestamibi/123I-BMIPP-mismatch, RR of 99mTc-sestamibi and RR of 123I-BMIPP were determined using traditional definition. The improvement of LV wall motion in the infarcted territory from acute phase to chronic phase was assessed using QGS. Results: Of 42 patients, the improvement of LV wall motion in the infarcted territory from acute phase to chronic phase was found in 29 patients. The presence of 99mTc-sestamibi/123I-BMIPP-mismatch and RR of 99mTc-sestamibi and RR of 123I-BMIPP were significantly linked to predict the improvement of LV wall motion (p=0.0001, p=0.0001 and p=0.002, respectively). To predict the improvement of LV wall motion in the infarcted territory in chronic phase, the presence of 99mTc-sestamibi/123I-BMIPP-mismatch showed sensitivity of 93%, specificity of 85% and accuracy of 91%, while RR of 99mTc-sestamibi and RR of 123I-BMIPP had sensitivities of 72%, 48%, specificities of 85%, 100% and accuracies of 76%, 64%, respectively. The multivariate discriminant analysis revealed that the combination of 99mTc-sestamibi/123I-BMIPP-mismatch, RR of 99mTc-sestamibi and RR of 123I-BMIPP best predicted the improvement of LV wall motion in the infarcted territory in chronic phase with sensitivity of 93%, specificity of 85% and accuracy of 91% (chi-square=40.6), compared with RR of 99mTc-sestamibi and RR of 123I-BMIPP only (sensitivity 79%, specificity 85% and accuracy of 81%, chi-square=16.9). Conclusions: The addition of 99mTc-sestamibi/123I-BMIPP-mismatch on RR of 99mTc-sestamibi and RR of 123I-BMIPP in patients with AMI, help better predict the improvement of LV wall motion in the infarcted territory in chronic phase. Funding Acknowledgement: Type of funding sources: None.